Utilization Application and System Geographical Information Website: Systematic Literature Review - Muhamad Rizky (International Journal of Information Engineering and Science, 2024)
Geographic Information Systems (GIS) have become essential technological tools for collecting, storing, processing, analyzing, and visualizing spatial data to support various human activities. The rapid advancement of information technology has significantly expanded the use of GIS, particularly through web-based platforms and mobile applications, enabling wider accessibility and real-time data utilization. This study focuses on analyzing the utilization of GIS applications and websites across multiple sectors and their contributions to improving efficiency, accuracy, and decision-making processes in daily life. The main objective of this research is to identify, evaluate, and synthesize recent developments in GIS implementation through a systematic literature review. Scientific articles were collected from reputable international and national journals published within the last five years (2018–2022). A total of 130 international journals and 100 national journals were initially identified through database searches. After applying relevance screening and inclusion criteria, 33 selected articles were analyzed in depth to extract key findings, application trends, and potential research gaps. The results show that GIS applications and web-based systems play a vital role in supporting various sectors. In education, GIS facilitates spatial mapping for industrial internship placement (PRAKERIN) and school zoning management. In healthcare, GIS assists in mapping healthcare facilities, including pharmacies and hospitals, to improve service accessibility. In transportation, GIS-based systems provide route planning, traffic monitoring, and public transport information to enhance mobility and reduce congestion. GIS applications are also increasingly applied in environmental monitoring, disaster management, urban planning, and natural resource management. Overall, this study emphasizes the growing importance of GIS technologies as strategic tools for data-driven decision-making and sustainable development. The findings are expected to provide valuable insights for researchers, practitioners, and policymakers in optimizing GIS-based solutions to improve public services and quality of life.